Antioxidative Activity of Ferrocenes Bearing 2,6-Di-Tert-Butylphenol Moieties - E. R. Milaeva; S. I. Filimonova; N. N. Meleshonkova; L. G. Dubova; E. F. Shevtsova; S. O. Bachurin; N. S. Zefirov (Bioinorganic Chemistry and Applications)
The antioxidative activity of ferrocenes bearing either 2,6-di-tert-butylphenol or phenyl groups has been compared using DPPH (1,1-diphenyl-2-picrylhydrazyl) test and in the study of the in vitro impact on lipid peroxidation in rat brain homogenate and on some characteristics of rat liver mitochondria. The results of DPPH test at 20∘C show that the activity depends strongly upon the presence of phenolic group but is improved by the influence of ferrocenyl fragment. The activity of N-(3,5-di-tert-butyl-4-hydroxyphenyl)iminomethylferrocene (1), for instance, was 88.4%, which was higher than the activity of a known antioxidant 2,6-di-tert-butyl-4-methylphenol (BHT) (48.5%), whereas the activity of N-phenyl-iminomethylferrocene 2 was almost negligible −2.9%. The data obtained demonstrate that the compounds with 2,6-di-tert-butylphenol moiety are significantly more active than the corresponding phenyl analogues in the in vitro study of lipid peroxidation in rat brain homogenate. Ferrocene 1 performs a promising behavior as an antioxidant and inhibits the calcium-dependent swelling of mitochondria. These results allow us to propose the potential cytoprotective (neuroprotective) effect of ditopic compounds containing antioxidant 2,6-di-tert-butylphenol group and redox active ferrocene fragment.